Awareness of Rights amongst Caregivers of Children with Disabilities: A Hospital-based Survey - Ritu Majumdar; Sonal Chauhan; Ravi Kumar Preenja; Shikha Bhatnagar Bhardwaj (Indian Journal of Physical Medicine & Rehabilitation)
Objective: This cross-sectional study aimed to assess the level of awareness amongst caregivers of children with disabilities regarding disability, disability certification, rights, benefits, welfare schemes and legislations for persons with disabilities. Design: A cross-sectional hospital-based survey was conducted as part of this study. Patients/Participants: Caregivers of children with locomotor disability and autism spectrum disorder, aged between 3 and 18 years and attending the Physical Medicine and Rehabilitation outpatient department were recruited for this study. Materials and Methods: After informed consent, a pre-structured pro forma was filled by the principal investigator/coprincipal investigators of this study. The pro forma consisted of demographic profile and 25 questions regarding disability, disability certification, rights and benefits and various government welfare schemes related to disability. Results: The study revealed a significant lack of awareness amongst caregivers regarding disability and government welfare schemes. Conclusion: The findings underscore the substantial ignorance about disability and negative beliefs amongst caregivers, contributing to the underutilisation of rehabilitation services. Enhancing awareness amongst healthcare professionals at the district and community levels regarding disability and welfare schemes could significantly improve the accessibility of these programmes.